Práxis corporal na perspectiva do “ser mais”: uma proposta pedagógica para Educação Física no Ensino Fundamental - Lacerda, Maria de Fátima de (2018)
This research presents a dialogue with the analysis of the theoretical and practical assumptions that base a pedagogical perspective of teaching for Physical Education in Elementary School in a Municipal School of Fortaleza, anchored in the concept of Corporal Praxis in the perspective of “being more”. Thus, from a dialogic, critical and reflexive action, research was carried out along with the lines of the Action Research in a qualitative approach, in which I make a brief account of my professional experience, as a researcher, and my relation with the research until the production of this work which carried out a pedagogical intervention in the final series of elementary education in Physical Education. The studies were carried out in three different moments: firstly, we developed the theoreticalmethodological foundations of the Body Praxis in the perspective of "being more"; secondly, we organized the didactic units that composed the experimental project with the 5th year students in 2016; finnaly, it occurred in the re-elaboration, implementation, description and analysis of the didactic units of the 6th year in 2017. For this we had as basic theoretical reference Paulo Freire, Vázques, Gadotti, Figueiredo e Silva. As instruments of analysis we used the reports of implementation of Didactic Units, the materials produced by the students, the dialogical circles in class and semistructured interviews. The result’s organization was performed according to the thematic analysis technique for categorization. The findings indicated that the categories 'praxis' and 'being more' were the most importants. Nevertheless, we identified that the dialogicity, the partner knowledge, amorosity, problematization, were also present in the analyzes. Therefore, in the dialogue with the students and reflection of the school routine, we conclude that the Body Praxis in the perspective of "being more", amidst the difficulties encountered in the process, contributes to the construction of a pedagogical perspective of teaching for Physical School Education, acting in the formation of students who are more critical, autonomous, participative, aware of themselves and committed to change their reality in the perspective of "being more", working to construct a critical, dialogic and transformative education.